Photo energy conversion using synchronous sequential circuit based diode clamp multilevel inverter - Kannan, R. (Institute of Electrical and Electronics Engineers Inc., 2017)
The multilevel inverter technology introduced for medium and high voltage, high power applications. This paper is proposed to control the diode clamp multilevel inverter by using a synchronous sequential circuit for photo energy conversion. The performance of the multilevel inverter has been improved in-terms of minimum output harmonics distortion, simpler structure, effortless fault identification, cost-effectiveness and low power consumption. This new control strategy has maintained the balanced voltages on the dc link capacitors. PV based five-level diode clamped multilevel inverter has been validated with single induction motor drive through MATLAB/Simulink simulation and tested experimentally through the prototype model. © 2016 IEEE.